Dasar Pengetahuan dan Kriteria Kebenaran Perspektif Barat dan Islam - Andre Nova Frarera; Mariyati Mariyati; Nur Khafifah Indriyani Batubara; Salminawati Salminawati; Rahmad Hidayat (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
There is no truth because it is influenced by external rather than internal forces, so people from all walks of life always want to know the truth.The existence of particular facts is the foundation of truth itself.In this instance, the scientific truth that has been tried and proven by science.In order to distinguish between fiction and fact in the context of human life, a successful strategy in human cognition is to use the five senses to gather truth and information, which is then processed through logical reasoning. As a result, the purpose of this article is to attempt to compare and contrast the Western and Islamic perspectives on reality using scientific evidence. This article primarily focuses on the advantages it will provide to Muslims and the general public.